(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2025)
For Tasso, the composition of the Mondo creato is not only a challenge in the field of sapiential poetry, but also determines the redefinition of the figure of the poet: against the tendentially defiladed posture adopted by the poet of the Liberata, the reader is now presented with a poet who is willing, on several occasions, to take the floor in order to provide indications on his own poetic actions. The silence, unusual for Tasso, in theoretical writings regarding the nature of this new poetry requires us to turn our gaze precisely to the places where the poet’s voice emerges in an attempt to define the coordinates of the poetry of the Mondo creato. The analysis of these places - now the proemes, now the similes, now the transitional sections - offers the portrait of a chiaroscuro grammar, the result of the presence of explicitly asserted norms, but constantly subject to the tension arising from their feared or concealed, but never a priori rejected, infringement.